Sakakibarana, a new genus of Gyponini (Hemiptera: Cicadellidae: Iassinae) from the Amazon Rainforest - Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda; Mejdalani, Gabriel (Zootaxa, 2017)
A new genus of Gyponini, Sakakibarana gen. nov., is proposed and its type species S. amazonica sp. nov. is described and illustrated based on specimens from the Amazon Rainforest of Northern Brazil (states of Amazonas and Pará) and French Guiana. The new genus can be distinguished from other members of the Gyponini by the following morphological features: robust body, short crown, crown and face transition distinct and subfoliaceous, pronotum strongly declivous, male pygofer with caudal process, and aedeagus with dorsal apodemes with a pair of processes. A discussion comparing the new genus with the related genus Tenuacia DeLong, 1977 is provided.